EARLY INTERVENTION PROGRAM WITH FAMILY ORIENTED (CASE STUDY ON CHILD WITH AUTISTIC PDD – NOS) - Adiansyah, Moch. Restu; Nurfitria, Karima (Proceedings of International Conference on Special Education, 2015)
Children growth process must be applied on early stage and so must the intervention steps. Applying early intervention might give an optimal effect on children growth and it can be a prevention to overcome the obstacle and aberration which might have come in the future. This research conducted early intervention with family as the closest environment to a child so it can create comfort atmosphere and time efficiency. Family and home is a cornerstone for child’s growth. With family as child’s growth support and home as natural setting for habitual action that forms child’s growth. The subject of this research is a child with DA as his initial which whom is detected with autistic PDD – NOS. the subject still can not communicate fluently, has a passive body language with unstable emotion. This research used descriptive method with observation data, interview, documentation and assessment as data collecting techniques. Triangulated data also has been conducted to the related parties such as teachers and family. From the data processing, the research can conclude and establish a family oriented early intervention program. They are, 1) Making growth aspect which will be intervened as priority that is from language aspect because on his 3 years old age, he communicates as if he were still 1, 5 years old. 2) Establishing language intervention program which is focused on developing the child’s communication skill on his peers, his eye contact, and his pronunciation with training and special therapy. 3) Considering parents’ potency in conducting the intervention program including, considering their time. 4) Discussing the program with the parents. 5) Conducting early intervention program. 6) Giving the child back to his parents with the same treatment that has to be conducted by them.